Enhancing e-banking security: using whirlpool hash function for card number encryption - Yaseen Khudhur, Doaa; Saad Hameed, Saif; M. Al-Barzinji, Shokhan (International Journal of Engineering and Technology, 2018)
The Internet played - and still - the key that continuously changing our ways of interaction with people. As a result, several electronic services had emerged allowing businesses to grow by effectively allowing wide and easy interaction with customers and other businesses. The security and privacy of information over the internet in general and in electronic services providers have been the focus of widely published studies and researches, such that several software and hardware based solutions or hybrid of both is required. E-banking services grown significantly in the last decade where all financial matters of customers and businesses can be done online, and therefore, e-banking security and privacy is important. In this paper, I propose the use of Whirlpool hash function to enhance the security of e-bank service providers by encrypting customerâ€™s card sensitive information. In addition, based on the review of several articles, I found that Whirlpool outperformed several hashing functions and resists several well-known attacks.Â Â